IDENTIFIKASI Candida sp DALAM URIN IBU HAMIL DI KLINIK RAMLAH PARJIB 1 SAMARINDA - Annisa Rahmawati (Akademi Kesehatan John Paul II Pekanbaru, 2022)
Based on the survey results, there are several pregnant women who experience symptoms of candidiasis vulvovaginal. All pregnant women who visited the Clinic Ramlah Parjib 1 Samarinda on 15 February 2022, admitted that they had never carried out laboratory tests such as examination of urine and vaginal secretions. This study aims to identify the Candida sp fungus in the urine of pregnant women at Clinic Ramlah Parjib 1 Samarinda. This type of research is descriptive and uses a consecutive sampling technique with a sample of 30 pregnant womens urine. Respondents in this study were pregnant women. Samples were obtained from the urine of pregnant women at Clinic Ramlah Parjib 1 Samarinda which met the inclusion and exclusion criteria, then microscopic tests. The results showed that 8 people had Candidiasis vulvovaginal , 26,7% were positive Candida sp and 22 people, 73,3% were negative Candida sp. In addition, the growth of contaminant but harmless fungi was found, namely Aspergillus sp as many as 6 samples with a percentage of 20%.